Comparison of surgical vs. non-surgical closure procedures for secundum atrial septal defect - Mazdar Helmy; Mulyadi M. Djer; Sudung O. Pardede; Darmawan B. Setyanto; Lily Rundjan; Hikari A. Sjakti (Paediatrica Indonesiana, 2013)
Backgi-ound Surgery has been the standard therapy for secundumatrial septa! defect (ASD) closure, but it has significant associatedmorbidities related to st ernotomy, car diopulmonary bypass,complications, residual scars, and trauma. A less invasive nonsurgicalapproach with transcatheter devices was developed toocclude ASD. AmplatzerÂ® septa! occluder (ASO) is a commondevice in transcatheter closure.Objective To compare two secundum ASD closure procedures,transcatheter closure by ASO and surgical closure, in terms ofefficacy, complications, length of hospital stay, and total costs.Methods A retrospective analysis was performed on childrenwith secundum ASD admitted to the Cardiology Center ofCipto Mangunkusumo Hospital from January 2005 to December2011. Patients received either transcatheter closure with ASOor surgical closure procedures. Data was obtained from patients'medical records.Results A total of 112 secundum ASD cases were included in thisstudy, consisting of 42 subjects who underwent transcatheter closureprocedure by ASO and 70 subjects who underwent surgical closureprocedure. Procedure efficacies of surgery and ASO were not significantlydifferent (98.6% vs 95.2%, respectively, P= 0.555). However,subjects who underwent surgical procedures had significantly morecomplication s than subjects who underwent transcatheter closureprocedure (60% vs 28.6%, respectively, OR 1.61; 95%CI 1.19 to2.18; P= 0.001). Hospital stays were also significantly longer forsurgical patients than for transcatheter closure patients (6 days vs2 days, respectively, P< 0.0001). In addition, all surgical subjectsrequired intensive care. Transcatheter closure had a mean total costof 52.7 (SD 6.7) million Rupiahs while the mean cost of surgery was47 (SD 9.2) million Rupiahs (P< 0.0001) . Since the ASO devicecost represented 58% of the total cost of transcatheter closure, themean cost of transcatheter closure procedure without the deviceitself was less costly than surgery.Conclusion Transcatheter closure using ASO has a similar efficacyto that of surgical closure procedure. However, subjects whounderwent transcatheter closure have lower complication ratesand shorter length ofhosp ital stays than subjects who had surgery,but transcatheter closure costs are higher compared to the surgicalprocedure.